LANGUAGE SYSTEM AND ITS STRUCTURAL FEATURES - Akramova K.A (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstact This study investigates the structure of the English language, examining the phonetic, morphological, syntactic, lexical, and semantic levels and their interrelationships. It demonstrates that each level performs specific functions while interacting to ensure clarity, coherence, and expressiveness in communication. The findings highlight the importance of understanding these patterns for language learning, effective communication, and language teaching.